The diagnostic value of prostate health index combined with soluble e-cadherin for prostate cancer - Ahamed, Yeasin; Hossain, Marofe; Baral, Shantanu; Chen, Jing; Sun, Weigui (Frontiers in Endocrinology, 2025)
ObjectiveTo assess the diagnostic value of combining prostate health index (PHI) and soluble epithelial cadherin (sE-cadherin) in prostate cancer (PCa) detection.MethodsThis study included 250 benign prostatic hyperplasia (BPH) and 250 PCa patients (2020–2024). PCa patients were categorized by disease stage (I-II:115; III-IV:135), bone metastasis (non-metastatic:171; metastatic:79), and Gleason score (≤8:136; >8:114). Serum sE-cadherin (ELISA), tPSA, fPSA, and p2PSA (chemiluminescence) were measured; PHI was calculated. ROC curves evaluated diagnostic performance.ResultssE-cadherin, tPSA, p2PSA, and PHI levels were significantly higher in PCa vs. BPH (P<0.05), with further elevations in advanced stages, metastatic cases, and Gleason >8 (P<0.05). ROC analysis demonstrated AUCs of 0.719 (sE-cadherin), 0.761 (PHI), and 0.792 (combined), indicating superior diagnostic accuracy for the combination.ConclusionCombining sE-cadherin and PHI enhances PCa detection accuracy, correlating with disease severity, metastasis, and aggressiveness.